Massage Punggung dapat Meningkatkan Nilai Arus Puncak Ekspirasi pada Anak Asma - I Nyoman Ribek (Jurnal Gema Keperawatan, 2017)
The purpose of this study was to determine the effect of back massage on expiratory peak current rate in asthmatic children in MangusadaBadung General Hospital. This research is a quantitative research with pre experimental group type pre-test posttest. The number of samples are 24 asthmatic children who visited MangusadaBadung General Hospital selected by incidental sampling technique. The data collection tool is an observation sheet and peak flow meter to measure the peak expiratory flow rate. Data analysis technique used in this research is univariate analysis for respondent characteristic and bivariate analysis to analyze pretest and posttest PEFR value. The result of mean analysis of PEFR value before treatment was 102,92 L / m, mean of APE value after treatment was 113,33 L / m, so the mean value difference was 10,41 L / m. The bivariate test uses paired-samples t test because the data distribution is normal. Result of research with significant value (p) = 0.000 which means p 0,05 with errorrate 5% then Ho (zero) is rejected which means back massage effect on peak expiratoryflow rate in children with asthma.